Edukasi Hukum Hak Atas Tanah Individual Memitigasi Sengketa di Kelurahan Lumpue Parepare - Mutiah Wenda Juniar; A. Suci Wahyuni; Andi Muhammad Aswin Anas; Ismail Iskandar; Arini Nur Annisa; A. Farina Aura Aulya; Dyandra Rayyani Hendra Putri; Abdi Ardiansyah; Tiara Karmen Visya Lagoan; Andi Besse Alfiyah (Cattleya Darmaya Fortuna, 2025)
Land rights are part of human rights guaranteed by the constitution as stipulated in Article 28H paragraph (4) of the 1945 Constitution. However, practice in the field shows that many people still face land disputes due to weak administration and a lack of legal understanding. In the Lumpue sub-district of Pare-Pare city, there were overlapping claims of land ownership and transfers of land rights under the table without involving a notary. This community service activity was aimed at providing legal education in the form of interactive and participatory discussions on the theme of Land Rights as Human Rights: Mitigating Land Disputes. The activity was carried out in three stages: a pretest, legal counseling, and a post-test. The counseling and discussion activities were held at the Lumpue Village Office in Pare-Pare City and were attended by community members, village office officials, and resource persons from the Pare-Pare City Land Office as well as academics with expertise in land law. The land issues faced by the community are diverse, such as transfer of rights without going through a PPAT (Land Deed Official), lack of land title certificates, boundary disputes, land measurement, land use taxes, and land use in coastal areas. This program successfully built legal awareness and strengthened the community's capacity to avoid land disputes and conflicts. The handling of disputes through the district/city land office needs to synergize with the local government, especially at the village and sub-district levels, so that the resolution of disputes experienced by the community can be optimized